Doppler sonographic evaluation of peripheral arterial disease and its associated factors among diabetes mellitus patients at Muhimbili National Hospital, Tanzania: A hospital-based cross-sectional study - James Alex Sumawe; Lilian Salingwa (PLoS ONE, 2026)
Background Peripheral arterial disease (PAD) is more common among patients with diabetes mellitus (DM) and can lead to critical limb ischemia and amputation. Data on Doppler-diagnosed PAD are scarce in Tanzania. This study aimed to determine the prevalence of PAD and associated risk factors among DM patients referred for lower limb Doppler assessment at a tertiary hospital. Patients with ≥Grade III stenosis according to Jager’s criteria were classified as having peripheral arterial disease. Methods Analytical cross-sectional design was conducted among 80 adult DM patients suspected of PAD at Muhimbili National Hospital between April 3, 2023, and March 30, 2024. Demographic, clinical, and sonographic data were collected. PAD was defined as ≥Grade III stenosis by Jager’s criteria. Associations between risk factors and PAD were analyzed using Firth penalized logistic regression to account for small event numbers. Results Mean participant age was 61.2 ± 11.2 years; 55% were male. 18% had PAD, and 63.7% had hypertension. The dorsalis pedis artery was the most commonly affected segment (32.5%). Only DM duration was significantly associated with PAD (AOR = 1.19; 95% CI: 1.00–1.41; p = 0.044). Conclusion PAD is present in a notable proportion of DM patients referred for Doppler evaluation. Longer DM duration is an exploratory predictor. Findings are limited by small sample size, few PAD events, and missing HbA1c data. Larger, multicenter studies are needed to confirm risk factors and improve generalizability.